STRATEGI ORANG TERINFEKSI HIV DALAM MEMANAJEMEN GEJALA EFEK TERAPI ANTIRETROVIRAL DI BALI - Raya, Nyoman Agus Jagat; Suarningsih, Ni Kadek Ayu (Coping: Community of Publishing in Nursing; Vol 11 No 4 (2023): Agustus 2023DO - 10.24843/coping.2023.v11.i04.p01, 2023)
Antiretrovirals (ARVs) are needed by people living with HIV (PLWH) to reduce the rate of HIV progression, however ARVs have side effects for some PLWH. Managing symptoms are very necessary to reduce uncomfortable symptoms that interfere with PLWH's activities. The aim of this study was to explore the experiences of PLWH in managing the symptoms of the effects of ARV therapy (ART) in Bali, Indonesia. This research used a qualitative study design with a phenomenological approach. The participant collection technique was through purposive sampling and snowball sampling techniques based on the criteria: people with HIV status aged 18 years or more and currently undergoing ART and domiciled in Bali. Semi-structured questions about symptom management strategies were used to elicit participants' experiences. Thematic analysis was used. Four themes were obtained from 10 participants who were willing to sign informed consent in this study, namely 1) symptom management strategies including medication, controlling thoughts, carrying out spiritual activities, diverting activities, and providing support; 2) reasons for symptom management were based on comfort and reduced symptoms; 3) symptom management information derived from internal and external sources; and 4) effectiveness of symptom management strategies including levels of effectiveness and satisfaction. An overview of data regarding effective strategies carried out personally by PLWH to reduce the symptoms as the effect of ART. HIV nurses can develop interventions plan such as health education or counseling related to symptom management strategies due to ARV side effect, especially for PLWH who are taking ARVs for the first time.